Effect of Nano-TiO2 Particles Surface Modification on Antibacterial Properties of Cotton Fabrics (Journal of Fiber Bioengineering and Informatics, 2018)
The dispersion property of modified nano-TiO_2 particles and its antibacterial properties on cotton fabrics were studied. The results show that the stability of nano-TiO_2 solgel was related to the concentration of the modifier and the pH values of the system. The experimental result shows that washing fastness of the finished fabric treated with modified nano-TiO_2 had been increased and the antibacterial property of finished fabric was also related to the concentration of the modifier.